Pedagogical leadership, new perspectives for teacher performance - Casas Mallma, Angela C. (2019)
The research objective is to demonstrate that there is a positive relationship between the principal’s pedagogical leadership and the teaching performance at the secondary level of "María Parado de Bellido" school, Rímac district, Lima - 2017. The research approach is quantitative with transactional design, and correlational type. The sample was 280 students, 44 teachers and 3 principals to whom a survey was applied. For the validation was made from the expert judgment, with a result of 92%, also used the Cronbach’s Alpha test, obtaining 0,916 of reliability, determining its internal consistency with very high tendency. The alternative hypothesis holds that there is a positive relationship between the principal’s pedagogical leadership and the teaching performance at the secondary school level under investigation. For the contrasting hypothesis, the Pearson correlation was used among the research study variables. As the Value p = 0.000 <0.05, the null hypothesis is rejected, and the alternative hypothesis is accepted. Therefore, both research variables have a direct correlation and reach a level of 0.897 that corresponds to a high positive correlation level. It is concluded that the greater principal’s pedagogical leadership will be the higher teachers’ performance levels. Similar manner, if the principal’s leadership does not prioritize his role as pedagogical leader as the center of his work, the teachers’ performance will be deficient.